2014
DOI: 10.1371/journal.pone.0097324
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein, ZFP36L2, Influences Ovulation and Oocyte Maturation

Abstract: ZFP36L2 protein destabilizes AU-rich element-containing transcripts and has been implicated in female fertility. In the C57BL/6NTac mouse, a mutation in Zfp36l2 that results in the decreased expression of a form of ZFP36L2 in which the 29 N-terminal amino acid residues have been deleted, ΔN-ZFP36L2, leads to fertilized eggs that arrest at the two-cell stage. Interestingly, homozygous ΔN-Zfp36l2 females in the C57BL/6NTac strain release 40% fewer eggs than the WT littermates (Ramos et al., 2004), suggesting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 47 publications
3
45
0
2
Order By: Relevance
“…ZFP36L2 (zinc finger protein 36‐like 2) is a murine homolog of Xenopus C3H‐4. A natural mutation of Zfp36l2 in mice that the N‐terminal 29 amino acid residues were deleted led to oocyte maturation and ovulation defects (Ball et al , ). A new study published during the submission of our paper further demonstrated that oocyte‐specific loss of Zfp36l2 causes oocyte maturation and fertilization defects by preventing global transcriptional silencing in GV oocytes (Dumdie et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…ZFP36L2 (zinc finger protein 36‐like 2) is a murine homolog of Xenopus C3H‐4. A natural mutation of Zfp36l2 in mice that the N‐terminal 29 amino acid residues were deleted led to oocyte maturation and ovulation defects (Ball et al , ). A new study published during the submission of our paper further demonstrated that oocyte‐specific loss of Zfp36l2 causes oocyte maturation and fertilization defects by preventing global transcriptional silencing in GV oocytes (Dumdie et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Maturation of mammalian oocytes is a complex physiological process involving a large number of regulatory factors, cell structures, and different signaling pathways (Ball et al, 2014;Dang-Nguyen et al, 2014;Prunskaite-Hyyryläinen et al, 2014). For example, the cyclic adenosine monophosphate (cAMP) signaling pathway is necessary for maintaining meiosis, whereas the MAPK signaling pathway plays an important role in meiosis initiation, spindle assembly, and M2 arrest.…”
Section: Discussionmentioning
confidence: 99%
“…These mice appeared normal but had complete female infertility, resulting in embryonic failure at approximately the two-cell stage. Further studies with these mutant mice suggested that ZFP36L2 could bind directly to the mRNA encoding luteinizing hormone receptor (LHR), which is necessary for hormonal functioning during reproduction [50]. …”
Section: Loss Of Function Mutationsmentioning
confidence: 99%